The Impact of Family Dynamics on Palliative Care at the End-of-Life - Neil A. Nijhawan; Rasha Mustafa; Aqeela Sheikh (Palliative Medicine and Hospice Care, 2024)
This commentary is the second in a series highlighting the challenges we face in providing palliative care. This case highlights the numerous, multifaceted issues that interplay in the complex web of physical and psycho-social dynamics that are always present but take on more significance towards the end of life. The rationale for documenting our experience, undoubtedly a shared experience among palliative care teams, is twofold: (1) as a form of narrative reflective debriefing and (2) to give context to the distress that we see manifested by families as a loved one enters the end-of-life (EoL) period.